METHOD OF CRITICALITY LEVEL ASSESSMENT FOR CRISIS MANAGEMENT SYSTEMS - Корченко, Анна Олександрівна; Козачок, Валерій Анатолійович; Гізун, Андрій Іванович (Ukrainian Information Security Research Journal, 2015)
Crisis influence on the security level of state informationresources, different organizations and whole state is veryserious. Crisis can stop system development that comesunder its influence and also it can crush the system in thebud. To prevent this influence the adequate (to threatslevel) measures and security means must be taken and itdefines the importance of current situation criticality assessment.There is no generally accepted universal criteriaand integrated parameter for criticality level assessment ofcrisis. That’s why defining of criticality level assessmentfor incident is actual and important scientific task. In thepaper the set of parameters for criticality level assessmentof crisis was introduced and also method for defining thecriticality level of crisis with expert approach and fuzzysets theory was proposed. These don’t require the statisticaldata gathering and processing. Besides the defazificationprocedure for parameters was described and on itsbase indicator of criticality level was built.